Improving Student Learning Outcomes With a Staffing Administration Module Based Guided Inquiry In Basic Competencies Suggested Leave Regulations - Dwi Novita Sari; I Nyoman Suputra; Amin Chasanah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this study is to (1) produce personnel administration learning module Guided Inquiry-based for XI graders of Vocational School, particularly for office administration expertise program based on basic competence point 3.6 (proposing leave regulation) and 4.6 (reciting leave regulation), (2) validate the product through the validation test, (3) and find out the different learning outcome for those who used and did not used this product. there are different learning outcomes from those who belong to the control and experimental class namely 10,81 (control class average score= 82,58 and experimental class average score= 93,39).